2022
DOI: 10.1097/ccm.0000000000005469
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Treatment of Adult Intensive Care Patients: A Systematic Review and Meta-Analysis

Abstract: To evaluate and synthesize the available literature on sex differences in the treatment of adult ICU patients. DATA SOURCES: MEDLINE and EMBASE.STUDY SELECTION: Two reviewers independently screened publications to identify observational studies of adult ICU patients that explicitly examined the association between sex and ICU treatment-specifically, mechanical ventilation, renal replacement therapy, and length of stay. DATA EXTRACTION:We extracted data independently and in duplicate: mean age, illness severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 52 publications
7
33
0
Order By: Relevance
“…The fact that the increased ICU mortality trend in relation to severity of illness in our study was no longer evident indicates that this trend is explainable by the admission of more severely ill patients over the years—which particularly affects the female population given their higher ICU mortality observed. Consistent with published literature, men with AMI in our study were also more frequently referred to reperfusion therapies and received more often organ support upon ICU admission and during ICU stay than women, including mechanical ventilation and vasoactive medication [ 34 , 42 ]. This phenomenon is known as the ‘Yentl Syndrome’ [ 43 ] and might be particularly pronounced in younger women [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…The fact that the increased ICU mortality trend in relation to severity of illness in our study was no longer evident indicates that this trend is explainable by the admission of more severely ill patients over the years—which particularly affects the female population given their higher ICU mortality observed. Consistent with published literature, men with AMI in our study were also more frequently referred to reperfusion therapies and received more often organ support upon ICU admission and during ICU stay than women, including mechanical ventilation and vasoactive medication [ 34 , 42 ]. This phenomenon is known as the ‘Yentl Syndrome’ [ 43 ] and might be particularly pronounced in younger women [ 44 ].…”
Section: Discussionsupporting
confidence: 86%
“…No difference has been reported in the incidence of sepsis-associated acute kidney injury in men and women [ 68 ]. However, a meta-analysis of 21 studies including a total of 545,538 participants revealed that females were less likely to receive renal replacement therapy compared with males (adjusted OR 0.81 [0.73–0.89], I 2 = 57.4%) [ 69 ].…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Additionally, the authors were not able to account for death as a competing risk when assessing the probability of receiving ICU resources. As Modra et al (8) previously showed, women are more likely to die in the ICU (10); such deaths shorten their ICU lengths of stay, resulting in less time in which mechanical ventilation or renal replacement therapy can be initiated.…”
mentioning
confidence: 95%
“…Modra et al (8) found that across a wide range of ICU patients, sex was associated with differential resource use even after adjusting for patient-level severity of illness and age. This is a necessary first step to identify that disparity exists between men and women in critical care practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation